Case report: An infantile lethal form of Albright hereditary osteodystrophy due to a GNAS mutation - Leclercq, Valérie (Clin Case Rep, 2018)
Germline loss‐of‐function GNAS mutations are associated with multiple phenotypes, depending on the parental origin of the mutant allele. Here, we describe an infantile lethal form of atypical pseudohypoparathyroidism type 1a or 1c with severe Albright's hereditary osteodystrophy phenotype, underlying the extremely variable expressivity of this syndrome.